Beyond bungee jumping: Designing bungee cord to teach hooke’s law in problem-solving lab - Sriyansyah, Syakti P.; Safari, Iman; Busyairi, Ahmad (Momentum: Physics Education Journal, 2024)
Physics instruction is critical for helping students develop thinking skills and practical skills through the engineering design process, however, they often find it difficult to apply the concepts of physics to solving real-world problems. Bungee jumping is one of the favorite real-world applications in Hooke’s law as it requires a physics calculation to design the bungee cord required to meet the specified safety criteria. The purpose of this study, therefore, was to investigate 35 high school student’s mastery of concepts on the behavior of the spring through the implementation of an engineering design process activity in the problem-solving laboratory instruction. A pre-experimental study with one group post-test design only was used to outline a problem-solving laboratory instruction and to assess students’ mastery of concepts after the instruction. We found that only 48% of students or fewer were able to make effective use of Hooke’s law to propose a solution and design a model related to the bungee cord problem. Although most students seemed to acquire a reasonable grasp of the energy concepts to solve the quantitative problems, it was found that there was a widespread tendency to improperly apply the conservation of energy concept to the context of jumping from a height in a qualitative problem. However, the physics behind designing bungee cords can be used to engage students in learning Hooke’s law. Such a hands-on pass-fail test of the student solutions provides them with more meaningful real experiences in applying physics calculation to a real solution.